Quality and Detergency Optimization, Liquid Detergent Preparation, Mahogany Seed Extract (Swietenia mahagoni) - Mela Yuliyanti; Vinsensius Maunia Singgih Husada; Halida Anwar Alzundi Fahrudi; Widiastuti Agustina Eko Setyowati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
The use of Linear Alkylbenzene Sulfonate(LAS) as a surfactant for making detergent can pollute aquatic ecosystem and agricultural soils. Mahogany seed extract can be used as a substitute for LAS because it contains saponin so that it can be used also as a foaming agent to remove dirt on clothes. This research aims to know the optimum liquid detergent formula seen from its suitability with SNI 06-4075-1996 about Liquid Washing Detergents, foam stability and detergency power. The research steps are (1) Making simplicia (2) Extracting mahogany seeds with ethanol solvent (3) Identification of saponin (4) Making liquid detergent preparations (5) Quality test, foam stability test and detergency power. The results showed that formula 2 with a ratio of mahogany seed extract : LAS is 2 : 1 is the most optimum formula because it appropiate with SNI, and has the best foam stability and detergency power. Formula 2 has pH 11.1; specific gravity 1.1; 0.1% free alkaline, foam stability of 70% and detergency without rinsing 91.53% and by rinsing 94.680%.